2008
DOI: 10.1002/jcp.21559
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells effectively reduce surgically induced stenosis in rat carotids

Abstract: Restenosis following vascular injury remains a pressing clinical problem. Mesenchymal stem cells (MSCs) promise as a main actor of cell-based therapeutic strategies. The possible therapeutic role of MSCs in vascular stenosis in vivo has been poorly investigated so far. We tested the effectiveness of allogenic bone marrow-derived MSCs in reduction of stenosis in a model of rat carotid arteriotomy. MSCs were expanded in vitro retaining their proliferative and differentiation potentiality. MSCs were able to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 55 publications
4
48
0
2
Order By: Relevance
“…These findings indicated that the characteristic immunophenotype of rat bone marrow-derived MSCs was exhibited in the isolated cells. [25][26][27] MSCs have the ability to differentiate into osteogenic and adipogenic lineages. 25,26 The cells described herein are able to differentiate into osteocytes and adipocytes (Fig.…”
Section: Characteristics Of Mscs Isolated From Rat Bone Marrowmentioning
confidence: 99%
“…These findings indicated that the characteristic immunophenotype of rat bone marrow-derived MSCs was exhibited in the isolated cells. [25][26][27] MSCs have the ability to differentiate into osteogenic and adipogenic lineages. 25,26 The cells described herein are able to differentiate into osteocytes and adipocytes (Fig.…”
Section: Characteristics Of Mscs Isolated From Rat Bone Marrowmentioning
confidence: 99%
“…These ultimately lead to excessive neointima formation and re-narrowing of the arterial lumen. Although its frequency has declined in recent years, the residual risk of restenosis after percutaneous and surgical revascularization has prompted ongoing evaluation of experimental strategies to prevent or treat its progression, including the administration of different progenitor cell types to facilitate normal arterial healing and avert aberrant, deleterious repair [3][4][5][6][7].…”
mentioning
confidence: 99%
“…To this end, Forte et al have previously reported that systemic infusion of allogeneic BM MSCs resulted in attenuation of inward remodeling and luminal narrowing thirty days into a rodent model of carotid artery crush and arteriotomy [3]. This surgical model has the important distinction from wire or balloon injury in that it creates a greater degree of arterial wall trauma by disrupting both the internal and external elastic lamina.…”
mentioning
confidence: 99%
“…Clearly, this method can be used for endovascular seeding of other cell types, such as EPCs. The rationale behind using MSCs in our study stems from robust data indicating that seeding of a sufficient number of MSCs on vascular grafts, 5,17 acellular bioprosthetic valves, 18 or injured vascular segments 6,7,19 leads to improved endothelialization and decreased neointimal formation, not necessarily by direct MSC endothelial differentiation, but likely via paracrine mechanisms. 19 To this point, MSCs secrete vascular endothelial growth factor, insulin-like growth factor, and hematopoietic growth factor, 20 stimulate endogenous angiogenesis, and have a positive effect on the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Another potentially attractive therapeutic cell is the bone marrow-derived mesenchymal stem cell (MSC), which has been shown to facilitate re-endothelialization of prosthetic vascular grafts 5 and to reduce neointimal formation after vascular injury. 6,7 One limitation to the development of cell therapy specifically for vascular healing is the lack of a delivery method that is efficacious in moving cells to, and arresting them at, the vascular wall under the conditions of high shear stress present in arteries. To this end, we hypothesized that acoustic radiation force can be employed to selectively displace therapeutic cells coated with microbubbles to a specific vascular segment (Fig.…”
mentioning
confidence: 99%